2018
DOI: 10.5664/jcsm.7230
|View full text |Cite
|
Sign up to set email alerts
|

Use of Actigraphy for the Evaluation of Sleep Disorders and Circadian Rhythm Sleep-Wake Disorders: An American Academy of Sleep Medicine Clinical Practice Guideline

Abstract: The following recommendations are intended as a guide for clinicians using actigraphy in evaluating patients with sleep disorders and circadian rhythm sleep-wake disorders, and only apply to the use of FDA-approved devices. Each recommendation statement is assigned a strength ("Strong" or "Conditional"). A "Strong" recommendation (ie, "We recommend…") is one that clinicians should follow under most circumstances. A "Conditional" recommendation (ie, "We suggest…") reflects a lower degree of certainty regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
181
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(194 citation statements)
references
References 7 publications
(13 reference statements)
3
181
1
3
Order By: Relevance
“…Additionally, most previous studies employed only a single mode of sleep assessment, while PROs and objective sleep outcomes (such as polysomnography and actigraphy) provide complementary information . Although polysomnography is considered the gold standard, in an ambulant setting objective sleep outcomes are best measured with actigraphy . Actigraphy provides quantitative sleep parameters such as sleep duration, wake after sleep onset, and sleep efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, most previous studies employed only a single mode of sleep assessment, while PROs and objective sleep outcomes (such as polysomnography and actigraphy) provide complementary information . Although polysomnography is considered the gold standard, in an ambulant setting objective sleep outcomes are best measured with actigraphy . Actigraphy provides quantitative sleep parameters such as sleep duration, wake after sleep onset, and sleep efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Actigraphy provides quantitative sleep parameters such as sleep duration, wake after sleep onset, and sleep efficiency. The sleep estimates obtained with actigraphy can contribute to our understanding of clinical sleep disorders . PROs provide valuable qualitative and subjective information on sleep behaviors and consequences of impaired sleep (such as bedtime routines, sleep anxiety, and daytime sleepiness) that cannot be assessed with actigraphy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep diaries are commonly used in sleep studies. Although the American Sleep Disorders Association recommended using the actigraphy and polysomnography for objectively assessing sleep in sleep research and sleep medicine (Kushida et al., ; Smith et al., ), certain sleep parameters such as sleep quality (SQ) may not be sufficiently explained by objective measures (Sadeh, ). Previous studies have shown that total sleep time (TST) and sleep efficiency (SE) measured using sleep diaries and those measured by actigraphy were not significantly different in patients with chronic musculoskeletal pain (Wilson, Watson, & Currie, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep diaries are commonly used in sleep studies. Although the American Sleep Disorders Association recommended using the actigraphy and polysomnography for objectively assessing sleep in sleep research and sleep medicine (Kushida et al, 2005;Smith et al, 2018), certain sleep parameters such as sleep quality (SQ) may not be sufficiently explained by objective measures (Sadeh, 2011).…”
mentioning
confidence: 99%